Assessing the Need of Syllabus Design for English Language for Madrasa Education at Secondary School Level: A Study on West Bengal Madrasas (Global Journal of Human-Social Science, 2020)
This study represents the present scenario and shortcomings of syllabus of English language inside the madrasas of West Bengal (WB), which need to be redesigned so as to give an inclusive outlook to the madrasa curriculum. Certain functional aspects of English language can be introduced with the modern teaching methods in madrasas so that they can be brought at par with mainstream or with other students who belong to other boards. Within the context of madrasa education and religious instruction, syllabus on communication skills in English needs restructuring to suit the present day requirements of vocational, technical and professional manpower. As the madrasa students fail in accessing social mobility, through diagnostic test, teachers' interview and textbook analysis (as part of methodology) this paper examines an increasing need for improving English language syllabus as a tool for modernization and bringing the madrasas at par with the educational institutions of national importance and higher learning.
Keywords: syllabus; english language; madrasa education; mainstream; communication skills; secondary school level